Integrative physiology and transcriptome reveal salt-tolerance differences between two licorice species: Ion transport, Casparian strip formation and flavonoids biosynthesis - Xin Li; Ying Xu; Jiade Zhang; Ke Xu; Xuerong Zheng; Jiafen Luo; Jiahui Lu (BMC Plant Biology, 2024)
Abstract Background Glycyrrhiza inflata Bat. and Glycyrrhiza uralensis Fisch. are both original plants of ‘Gan Cao’ in the Chinese Pharmacopoeia, and G. uralensis is currently the mainstream variety of licorice and has a long history of use in traditional Chinese medicine. Both of these species have shown some degree of tolerance to salinity, G. inflata exhibits higher salt tolerance than G. uralensis and can grow on saline meadow soils and crusty saline soils. However, the regulatory mechanism responsible for the differences in salt tolerance between different licorice species is unclear. Due to land area-related limitations, the excavation and cultivation of licorice varieties in saline-alkaline areas that both exhibit tolerance to salt and contain highly efficient active substances are needed. The systematic identification of the key genes and pathways associated with the differences in salt tolerance between these two licorice species will be beneficial for cultivating high-quality salt-tolerant licorice G. uralensis plant varieties and for the long-term development of the licorice industry. In this research, the differences in growth response indicators, ion accumulation, and transcription expression between the two licorice species were analyzed. Results This research included a comprehensive comparison of growth response indicators, including biomass, malondialdehyde (MDA) levels, and total flavonoids content, between two distinct licorice species and an analysis of their ion content and transcriptome expression. In contrast to the result found for G. uralensis, the salt treatment of G. inflata ensured the stable accumulation of biomass and total flavonoids at 0.5 d, 15 d, and 30 d and the restriction of Na+ to the roots while allowing for more K+ and Ca2+ accumulation. Notably, despite the increase in the Na+ concentration in the roots, the MDA concentration remained low. Transcriptome analysis revealed that the regulatory effects of growth and ion transport on the two licorice species were strongly correlated with the following pathways and relevant DEGs: the TCA cycle, the pentose phosphate pathway, and the photosynthetic carbon fixation pathway involved in carbon metabolism; Casparian strip formation (lignin oxidation and translocation, suberin formation) in response to Na+; K+ and Ca2+ translocation, organic solute synthesis (arginine, polyamines, GABA) in response to osmotic stresses; and the biosynthesis of the nonenzymatic antioxidants carotenoids and flavonoids in response to antioxidant stress. Furthermore, the differential expression of the DEGs related to ABA signaling in hormone transduction and the regulation of transcription factors such as the HSF and GRAS families may be associated with the remarkable salt tolerance of G. inflata. Conclusion Compared with G. uralensis, G. inflata exhibits greater salt tolerance, which is primarily attributable to factors related to carbon metabolism, endodermal barrier formation and development, K+ and Ca2+ transport, biosynthesis of carotenoids and flavonoids, and regulation of signal transduction pathways and salt-responsive transcription factors. The formation of the Casparian strip, especially the transport and oxidation of lignin precursors, is likely the primary reason for the markedly higher amount of Na+ in the roots of G. inflata than in those of G. uralensis. The tendency of G. inflata to maintain low MDA levels in its roots under such conditions is closely related to the biosynthesis of flavonoids and carotenoids and the maintenance of the osmotic balance in roots by the absorption of more K+ and Ca2+ to meet growth needs. These findings may provide new insights for developing and cultivating G. uralensis plant species selected for cultivation in saline environments or soils managed through agronomic practices that involve the use of water with a high salt content.